Evaluating an institutional health partnership using the ESTHER EFFECt tool: A case study of an evaluation of the institutional health partnership between Nigeria CDC and Public Health England - Ahmed Razavi; Ngozi Erondu; Katie Haddock; Gurnam Johal; Oyeronke Oyebanji; Chikwe Ihekweazu; Ebere Okereke (Elsevier, 2021)
Objectives: Bilateral Institutional Health Partnerships (IHPs) are a means of strengthening health systems and are becoming increasing prevalent in global health. Nigeria Centre for Disease Control (NCDC) and Public Health England (PHE) have engaged in one such IHP as part of Public Health England's International Health Regulations Strengthening project. Presently, there have been limited evaluations of IHPs resulting in limited evidence of their effectiveness in strengthening health systems despite the concept being used across the world. Study design: Qualitative, using a validated tool. Methods: The ESTHER EFFECt tool was used to evaluate the IHP between NCDC and PHE. Senior leadership from both organisations participated in a two-day workshop where their perceptions of various elements of the partnership were evaluated. This was done through an initial quantitative survey followed by a facilitated discussion to further explore any arising issues. Results: This evaluation is the first published evaluation of a bilateral global health partnership undertaken by NCDC and PHE. NCDC scores were consistently higher than PHE scores. Key strengths and weaknesses of the partnership were identified such as having wide ranging institutional engagement, however needing to improve dissemination mechanisms following key learning activity. Conclusions: There is a dearth of evidence measuring the effectiveness of international health partnerships; of the studies that exist, many are lacking in academic rigour. We used the ESTHER EFFECt tool as it is an established method of evaluating the progress of the partnership, with multiple previous peer-reviewed publications. This will hopefully encourage more organisations to publish evaluations of their international health partnerships and build the evidence base.